2020
DOI: 10.1007/s00281-019-00773-0
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of human papillomavirus transcription in the productive virus life cycle

Abstract: Human papillomaviruses (HPV) are a large family of viruses which contain a circular, double-stranded DNA genome of approximately 8000 base pairs. The viral DNA is chromatinized by the recruitment of cellular histones which are subject to host cell-mediated post-translational epigenetic modification recognized as an important mechanism of virus transcription regulation. The HPV life cycle is dependent on the terminal differentiation of the target cell within epithelia-the keratinocyte. The virus life cycle begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 103 publications
(132 reference statements)
1
77
0
6
Order By: Relevance
“…The coding regions of the viral genome contain between seven and nine open reading frames that are organized into early and late regions; the early region encodes the E1, E2, E1^E4, E8^E2, E5, E6, and E7 proteins and the late region encodes the L1 and L2 capsid proteins. The non-coding region, otherwise known as the upstream regulatory region (URR), is located upstream of the early region and contains multiple cis regulatory elements required for transcription, as well as the origin of replication [ 17 ]. Transcription from the viral genome occurs in three phases (early, intermediate, and late) and is intricately linked to the host epithelial differentiation program.…”
Section: Hpv Genomementioning
confidence: 99%
“…The coding regions of the viral genome contain between seven and nine open reading frames that are organized into early and late regions; the early region encodes the E1, E2, E1^E4, E8^E2, E5, E6, and E7 proteins and the late region encodes the L1 and L2 capsid proteins. The non-coding region, otherwise known as the upstream regulatory region (URR), is located upstream of the early region and contains multiple cis regulatory elements required for transcription, as well as the origin of replication [ 17 ]. Transcription from the viral genome occurs in three phases (early, intermediate, and late) and is intricately linked to the host epithelial differentiation program.…”
Section: Hpv Genomementioning
confidence: 99%
“…Cervical carcinogenesis is driven by the viral oncoproteins, E6 and E7. Their transcription and the HPV productive life cycle in differentiated epithelium relies on interactions with multiple cellular proteins and complex epigenetic remodelling of the viral chromatin, including both histone modifications and DNA methylation 5 . This epigenetic programme is disrupted during malignant transformation.…”
Section: Dna Methylation and Cervical Carcinogenesismentioning
confidence: 99%
“…One study showed that HPV16 p670 late promoter was highly methylated in cervical carcinoma cases [21]. The low expression of viral early gene and lack of capsid L1/L2 proteins expression in undifferentiated basal cells could prevent activation of immune response to viral infection [22].…”
Section: Introductionmentioning
confidence: 99%